Post‐exercise neural plasticity is augmented by adding blood flow restriction during low work rate arm cycling - Mikaela L. Frechette; Summer B. Cook; Brendan R. Scott; Jane Tan; Ann‐Maree Vallence (Experimental Physiology)
Abstract Blood flow restriction (BFR) combined with low work rate exercise can enhance muscular and cardiovascular fitness. However, whether neural mechanisms mediate these enhancements remains unknown. This study examined changes in corticospinal excitability and motor cortical inhibition following arm cycle ergometry with and without BFR. Twelve healthy males (24 ± 4 years) completed four, randomized 15‐min arm cycling conditions: high work rate (HW: 60% maximal power output), low work rate (LW: 30% maximal power output), low work rate with BFR (LW‐BFR) and BFR without exercise (BFR‐only). For BFR conditions, cuffs were applied around the upper arm and inflated to 70% of arterial occlusion pressure continuously during exercise. Single‐pulse transcranial magnetic stimulation was delivered to left primary motor cortex (M1) to elicit motor‐evoked potentials (MEP) in the right biceps brachii during a low‐level isometric contraction. MEP amplitude and cortical silent period (cSP) duration were measured before and 1, 10 and 15 min post‐exercise. MEP amplitude increased significantly from baseline to Post‐10 and Post‐15 for both the HW (both z < −7.07, both P < 0.001) and LW‐BFR conditions (both z < −5.56, both P < 0.001). For the LW condition without BFR, MEP amplitude increased significantly from baseline to Post‐10 (z = −3.53, P = 0.003) but not Post‐15 (z = −1.85, P = 0.388). The current findings show that HW arm cycling and LW‐BFR led to longer‐lasting increases in corticospinal excitability than LW arm cycling alone. Future research should examine whether the increased corticospinal excitability is associated with the improvements in muscle strength observed with BFR exercise. A mechanistic understanding of BFR exercise improvement could guide BFR interventions in clinical populations.